THE RELATIONSHIP BETWEEN EXPOSURE TO CIGARETTE-BASED MEDIA AND THE SMOKING BEHAVIOUR OF MALE TEENAGERS AT MAN 2 WONOSOBO - Mulyani, Sri; Alviana, Fifi; Setyawativ, Ari; Mustajab, Abdullah Azam; Purnamasari, Ika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Background: Smoking is a major trigger for several long-term (chronic) diseases that can lead to death. According to the 2019 Global Youth Tobacco Survey, 19.20% of students in Indonesia are active smokers, and 65.2% of students are also freely exposed to cigarette advertising. The high prevalence of smoking can impact various aspects, ranging from health, the environment, and the economy, both on a small and large scale. Objective: The purpose of this study was to determine the relationship between media exposure to cigarettes and smoking behavior among male adolescents at MAN 2 Wonosobo. Method: This study was quantitative, with an observational analytical method and a cross-sectional design. The sample in this study consisted of 36 individuals and was selected using a purposive sampling technique. Data analysis was performed using the Spearman correlation test. Results: The results of the univariate analysis showed that media exposure about cigarettes among adolescents was predominantly through television (91.7%) and billboards/large banners on the street (91.7%). Teenagers smoke in coffee shops (8.3%), homes (13.9%), public places (11.1%), and anywhere (5.6%). Conclusion: The Spearman correlation test showed a p-value of 0.235 (p>0.05), indicating no relationship between media exposure and smoking behavior among male adolescents at MAN 2 Wonosobo.